Youngia purpimea (Asteraceae), a new species from Sichuan, China - Peng, Yu-Lan; Ju, Wen-Bing; Gao, Xin-Fen; Gao, Yun-Dong (Phytotaxa, 2015)
Youngia purpimea, a new species from southern Sichuan, China, is described and illustrated. This species is morphologically most similar to Y. szechuanica and Y. zhenyiana by having capitula with five yellow florets, but differs from the latter two by having leathery and undivided caudical leaves being glabrous on both surfaces and purplish red abaxially, leaf margins sparsely dentate, and also by brown pappus.